Prostaglandin E2 imprints a long-lasting effect on dendritic cell progenitors in the bone marrow. Issue 2 (27th August 2013) - Scott, Naomi M; Ng, Royce L X; Gorman, Shelley; Norval, Mary; Waithman, Jason; Hart, Prue H
Abstract : Prostaglandin E2 attenuates systemic immune responses by modulating dendritic cell progenitors in the bone marrow. ABSTRACT: Dendritic cells (DCs) that differentiate in vitro from the bone marrow (BM) of mice with prostaglandin E2 (PGE2 )-associated inflammation of the skin, airways, or peritoneal cavity poorly initiate immune responses. To remove in vitro differentiation and allow BM-derived DCs to seed the periphery under steady-state conditions, as well as study the molecule proposed responsible, chimeric mice were engrafted for >16 wk with BM cells from mice exposed to PGE2 . Serial PGE2 -chimeric mice were established with BM cells from the primary chimeric mice. Immune responses in the airways and skin of the PGE2 -chimeric mice and serial PGE2 -chimeric mice were significantly attenuated. After inflammatory challenges by intranasal LPS, topical fluorescein isothiocyanate, and intraperitoneal alum, DCs, macrophages, and neutrophils trafficked poorly in PGE2 -chimeric mice and serial PGE2 -chimeric mice. Injection of BM-differentiated DCs from nonchimeric mice restored the reduced immune responses of PGE2 -chimeric mice. DCs from BM of 16-wk-engrafted PGE2 -chimeric and serial PGE2 -chimeric mice resembled cells differentiated from BM exposed to PGE2 for only 3 d, demonstrating the long-lasting effect of PGE2 on DC progenitors. PGE2 attenuates systemic immune responses by modulating myeloid cell progenitors in the BM such that BM-derived, terminally differentiated myeloid cells have poor trafficking ability to sites of need.